EVALUATION OF SOIL PROPERTIES AT DUMPSITES FOR AGRICULTURAL USE IN GWAGWALADA AND BWARI AREA COUNCILS, FEDERAL CAPITAL TERRITORY, NIGERIA - Innocent Udofot, Inemesit; Kudende Samaila, Ishaya; Joshua Magaji, Innocent; Anthonia Abugu, Nkechinyere (African Journal of Social and Behavioural Sciences, 2024)
Studies in the Federal Capital Territory (FCT) have not been able to determine the safety of dumpsite soils for agricultural use despite the widespread use of dumpsite soils as organic manure. A study of soil properties at dumpsites for agricultural use in the Gwagwalada and Bwari area councils was carried out with the following objectives: assess the concentration of soil properties at dumpsites in the study area; and then ascertain the suitability of soil at dumpsites for agricultural use in the study area. A field survey of three purposely selected dumpsites (Mpape, Gwagwalada and Kwuba) was conducted for the collection of soil samples. A total of eighty-one (81) soil samples were collected from the dumpsites and control sites. Three top and subsoil samples were collected at 0 m, 20 m, 40 m and 60 m from the three dumpsites and their control sites. The data were analysed via means, standard deviations and ANOVA. The results show that the mean distributions of soil properties at the Mpape, Gwagwalada and Kubwa dumpsites were as follows: pH (7.52, 7.52 and 7.08), EC (581.35, 264.75 and 906.50 μmol/cm), NO3- (15.11, 11.20 and 10.98 mg/kg), P (4.11 and 3.81 mg/kg), K (14.12 and 14.10 and 13.53 mg/kg), Zn (0.84 and 0.94 mg/kg), Pb (0.15 and 0.24 and 0.03 mg/kg), Cr (0.36 and 0.73 mg/kg), Cd (1.34 and 0.97 and 0.94 mg/kg), and Cu (1.75 and 1.49 mg/kg). The distributions of the soil properties were not uniform among the three dumpsites. It was concluded that the soils are not suitable for agricultural purposes. It is recommended, among other things, that soils at dumpsites should not be converted to agricultural use without treatment because of elevated heavy metals at dumpsites.